Tetanus toxin: convulsant action on mouse spinal cord neurons in culture - Bergey, GK (J Neurosci, 1983)
The effects of direct application of tetanus toxin on fetal mouse spinal cord neurons in culture are described. Tetanus toxin produces increased excitation characterized by paroxysmal depolarizing events (PDE). In contrast to the abrupt onset of convulsant action produced by postsynaptic glycine antagonist strychnine, the convulsant action of tetanus occurs after a dose-dependent latent period. The onset of the convulsant action of tetanus toxin is paralleled by a reduction in observed spontaneous inhibitory synaptic potentials. Excitatory synaptic events can be identified as components of some tetanus-PDE. The toxin does not alter postsynaptic responses to the inhibitory amino acids glycine and gamma-aminobutyric acid. The latency and convulsant action of tetanus toxin are consistent with an irreversible presynaptic membrane interaction that reduces inhibitory transmission, a mechanism of action distinct from those of convulsants that antagonize inhibitory transmitters at the postsynaptic membrane.